The behavior of coastal communities on management of domestic wastewater in Ternate City, Indonesia. Issue 1 (October 2020) - Nagu, N; Lessy, M R
Abstract: Coastal area is a region that highly vulnerable to environmental degradation. One of the problems occurred in the coastal area in Ternate city is the number of solid and liquid household waste throws to the watershed or sea water. The different of geographical characteristics in Ternate is the focus of this study. The study took place in Kampung Makassar Timur Village that has people who have the house on the sea water and Sangadji village who live in the coastal area. This research aims to determine the behaviour of the population in residential areas who live in different geographical characteristics by calculating a total load of domestic wastewater and measuring the quality of domestic wastewater. Data collection and information collected by using questionnaires to the respondents in the study areas and following up by determining the quality of wastewater in some representative stations by laboratory analyses performed. The result shows that the behaviour of most respondents indicate the same behaviour in disposing the domestic wastewater directly to the sea because of it is an easy way to throw the wastewater, while other mentioned there is no wastewater drainage available at their place.